Pleistocene Mollusca of Three Southeastern Michigan Marl Deposits - Mark Jeffrey Camp (Hello World!, 1974)
A study of mollusks from continuous columns of sediment from Little Goose Lake, Lime Lake, and Marl Lake in southeastern Michigan provided data on the later stages of lake history. The three lakes probably formed as ice block depressions between 14,000 and 13,500 years B.P. during the waning of the Carey Subage. Marl Lake and Lime Lake lie in Saginaw lobe deposits. Little Goose Lake is situated in the Erie-Saginaw interlobate area.